Phytopathogenic Bacteria and Plant Diseases - Thind, B. S. (Milton : CRC Press LLC, 2019)
The field of Phytobacteriology is rapidly advancing and changing, because of recent advances in genomics and molecular plant pathology, but also due to the global spread of bacterial plant diseases and the emergence of new bacterial diseases. So, there is a need to integrate understanding of bacterial taxonomy, genomics, and basic plant pathology that reflects state-of-the-art knowledge about plant-disease mechanisms. This book describes seventy specific bacterial plant diseases and presents up-to-date classification of plant pathogenic bacteria. It would be of great help for scientists and researchers in conducting research on ongoing projects or formulation of new research projects. The book will also serve as a text book for advanced undergraduate and postgraduate students of disciplines of Phytobacteriology and Plant Pathology. Contains latest and updated information of plant pathogenic bacteria till December 2018 Describes seventy specific bacterial diseases Presents classification of the bacteria and associated nomenclature based on Bergey's Manual Systematic Bacteriology and International Journal of Systematic and Evolutionary Microbiology Discusses practical and thoroughly tested disease management strategies that would help in controlling enormous losses caused by these plant diseases Reviews role of Type I-VI secretion systems and peptide- or protein-containing toxins produced by bacterial plant pathogens Briefs about plants and plant products that act as carriers of human enteric bacterial pathogens, like emphasizing role of seed sprouts as a common vehicle in causing food-borne illness Dr B. S. Thind was ex-Professor-cum-Head, Department of Plant Pathology, Punjab Agricultural University Ludhiana, India. He has 34 years of experience in teaching, research, and transfer of technology. He has conducted research investigations on bacterial blight of rice, bacterial stalk rot of maize, bacterial blight of cowpea, bacterial leaf spot of green gram, bacterial leaf spot of chillies and bacterial soft rot of potatoes. He also acted as Principal Investigator of two ICAR-funded research schemes entitled, "Detection and control of phytopathogenic bacteria from cowpea and mungbean seeds from 1981 to 1986 and "Perpetuation, variability, and control of Xanthomonas oryzae pv. oryzae, the causal agent of bacterial blight of rice" from 1989 to 1993, and also of a DST funded research scheme "Biological control of bacterial blight, sheath blight, sheath rot, and brown leaf spot of rice" from 1999 to 2002. He also authored a manual entitled, "Plant Bacteriology" and a text book entitled, "Phytopathogenic Procaryotes and Plant Diseases" published by Scientific Publishers (India). He is Life member of Indian Phytopathological Society, Indian Society of Plant Pathologists, Indian Society of Mycology and Plant Pathology, and Indian Science Congress Association.
4.3.1.1 Pathovar Concept4.3.1.2 International Standards for Naming Pathovars of Phytopathogenic Bacteria; 4.3.1.3 Genera of Phytopathogenic Bacteria; References; Chapter 5: Molecular Mechanisms of Virulence and Pathogenesis; 5.1 Quorum Sensing; 5.2 Role of Pathogenicity Factors in Disease Development; 5.2.1 Bacterial Secretion Systems; 5.2.1.1 Type I Secretion System; 5.2.1.2 Type II Secretion System; 5.2.1.3 Type III Secretion System; 5.2.1.4 Type IV Secretion System; 5.2.1.5 Type V Secretion System; 5.2.1.6 Type VI Secretion System
Description based upon print version of record.
5.2.1.7 Twin-Arginine Translocation Protein Secretion System
OCLC-licensed vendor bibliographic record.
Keywords: Bacterial diseases of plants; Phytopathogenic bacteria; SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / General; TECHNOLOGY / Agriculture / General